Small and medium-sized enterprises and corporate social responsibility: a systematic literature review - Tarquinio, Lara; Posadas, Stefanie Carolina (Piccola Impresa / Small Business, 2019)
A great number of studies related to Corporate Social Responsibility (CSR) have been published in recent decades, but only a limited amount of research has been dedicated to small and medium-sized entreprises (SMEs). Through a systematic review of academic literature of the last 15 years, our study aims to analyse the current state of research on CSR in SME contexts. In particular this study analyses theoretical viewpoints, methodological approaches, important results obtained from research, as well as suggestions for future studies on this topic. Our study may be valuable to both CSR scholars and practictioners, so as to promote and stimulate new research and applications in this area.